ELS155 : E-content publishing / Academy of Language Studies - UiTM, Academy of Language Studies (Universiti Teknologi MARA (UiTM), 2022)
This course aims to expose students to the development of e-content publishing. This course encourages students to be responsible for publishing e-content from its planning stage to editing process using various skills, software and technology. Through this course, students are able to understand the importance of exploring the experience of creating electronic publications in the workplace.